The protective effect and mechanism of catalpol on high glucose-induced podocyte injury - Yan Chen; Qingpu Liu; Zengfu Shan; Yingying Zhao; Meng Li; Baiyan Wang; Xiaoke Zheng; Weisheng Feng (BMC, 2019)
Abstract Background Catalpol, a natural iridoid glycoside in Rehmannia glutinosa, can alleviate proteinuria associated with diabetic nephropathy (DN), however, whether catalpol has a protective effect against podocyte injury in DN remains unclear. Methods In this study, we used a high glucose (HG)-induced podocyte injury model to evaluate the protective effect and mechanism of catalpol against HG-induced podocyte injury. Cell viability was determined by the 3-(4,5-dimethylthiazolyl-2-yl)-2,5-diphenyltetrazolium bromide (MTT) method. The levels of lactate dehydrogenase (LDH), superoxide dismutase (SOD) and malondialdehyde (MDA) were measured by commercial assay kits. Cell apoptosis and reactive oxygen species (ROS) were determined by using flow cytometry. Tumour necrosis factor α (TNF-α), interleukin-1β (IL-1β) and interleukin-6 (IL-6) levels were determined by enzyme-linked immunosorbent assay (ELISA). The protein expression levels of B-cell lymphoma-2 (Bcl-2), Bcl2-associated x (Bax), cleaved caspase-3, nicotinamide adenine dinucleotide phosphate oxidase enzyme 4 (NOX4), toll-like receptor 4 (TLR4), myeloid differentiation primary response gene 88 (MyD88), p38 mitogen-activated protein kinase (p38 MAPK), phosphorylated p38 MAPK (p-p38 MAPK), nuclear factor kappa B inhibitor alpha (IκBα) and phosphorylated IκBα (p-IκBα) were measured by western blotting. In addition, Bcl-2, Bax, caspase-3 and nuclear factor kappa B (NF-κB) levels were determined by immunofluorescence staining. Results Catalpol significantly increased cell viability and decreased LDH release in HG-induced podocyte injury. Catalpol significantly decreased ROS generation, apoptosis, level of MDA, levels of inflammatory cytokine TNF-α, IL-1β, and IL-6 and increased SOD activity in HG-induced podocyte injury. Moreover, catalpol significantly decreased expression of cleaved caspase-3, Bax, NOX4, TLR4, MyD88, p-p38 MAPK, p-IκBα and NF-κB nuclear translocation, as well as increased Bcl-2 expression in HG-induced podocyte injury. Conclusion Catalpol can protect against podocyte injury by ameliorating apoptosis and inflammation. These protective effects may be attributed to the inhibition of NOX4, which alleviates ROS generation and suppression of the TLR4/MyD88 and p38 MAPK signaling pathways to prevent NF-κB activation. Therefore, catalpol could be a promising drug for the prevention of DN.